Changes in the use of natural resources in a Popoloca community in the State of Puebla - Bustamante González, Angel; García Maceda, Jesús; Vargas López, Samuel (Agricultura, Sociedad y Desarrollo, 2023)
This study interprets how the relationship of the inhabitants of the community of San Felipe Otlaltepec, Puebla, Mexico, with the natural resources of their territory has changed, using information taken from the local actors them and by comparing perceptions over a 30 year period. The interaction between man and nature, particularly the role of the latter as the main subsistence provider in rural communities, is subject to notable changes due to endogenous and exogenous factors. In the absence of local studies indicating local use of natural resources, the oral information obtained from the areas inhabitants enabled us to assess these dynamics of change. Through interviews with key informants and the application of questionnaires to 154 farmers, we developed a model for the use of local natural resources and evaluated perceived changes in their agricultural, livestock and forestry systems. The farmers interviewed perceived changes in their agricultural production system and in the use of local natural resources, particularly concerning livestock grazing, cultivated area, crop yield, number of goats in the family unit and use of firewood (extraction from the forest and its purchase). We concluded that the direct use of the natural resource and the crop of greatest importance to the interviewees (maize) relate to the interviewees’ perception of the change in the use of natural resources and agricultural systems.